Survey and mapping of the leading causes of childhood mortality in Nigerian tertiary hospitals - Smith, Stella I; Nwaokorie, Francisca O; Adagbada, Ajoke O; Yisau, Jacob I; David, Nkiru A; Adeboye, Muhammed A N; Adesida, Solayide A; Bamidele, Moses; Adeneye, Adeniyi; Fowora, Muinah A; Musa, Zaidat A; Adedeji, M A; et al. (Indian Journal of Child Health, 2016)
Background: Despite the modest gains made under the millennium development goals, indices of child health for Nigeria remain poor. Improvement on these indices requires mitigating the causes of childhood mortality. Objective: We undertook this study to determine the leading cause(s) of childhood mortality in Nigeria from 2005 to 2009. Methods: Using stratified random sampling techniques, data on demographics and cause(s) of death of under-five children, who had died between 2005 and 2009, were collected from the patients’ records of seven teaching hospitals. Data were analyzed using IBM SPSS version 20.0. Results: The leading causes of childhood mortality from this survey were neonatal sepsis (30.1%), asphyxia (27.2%), preterm complications (25.8%), and acute respiratory illness (15.3%). Analysis of causes of death by geopolitical zones did not indicate any definite pattern, although the North-Central and South-West had the highest deaths due to respiratory tract infections. The highest death records from human immunodeficiency virus/acquired immune deficiency syndrome came from North-East. In addition, Lagos in South-West was the most likely to have recorded death due to malaria (p<0.05). Preterm complications and neonatal sepsis accounted for the majority of the causes of death in low birth weight babies, whereas neonatal sepsis and asphyxia accounted for the majority of the causes of death in the appropriate birth weight group. Conclusions: This study supports the results of previous ones that childhood mortality was due to illnesses that were preventable and treatable. Knowledge of the causes and pattern of childhood mortality is essential to enable the health authorities to scale up appropriate interventions to reduce the burden. This will help the country to meet the target of reducing under-five mortality by two-thirds, few years after 2015.